The Layered Architecture of Clinical Objectivity: How Aesthetic Bias Interacts with Structured Psychopathy Assessment - Citra Permata Sari Saputri (Buletin Psikologi, 2026)
Psychopathy assessment, though methodologically rigorous, remains cognitively permeable to automatic perceptual inputs. This integrative review examines how aesthetic bias—specifically facial trustworthiness and attractiveness—shapes the interpretation of psychopathy-related traits and subsequent legal outcomes. We propose a sequential framework illustrating how bias propagates from neural appraisal to clinical interpretation and institutional consequence. Findings suggest that aesthetic bias operates as a probabilistic judgment shaper, primarily affecting the interpersonal-affective criteria of Factor 1. This process is explained through a dual-process account: rapid System 1 facial inferences form a perceptual anchor that System 2 deliberative reasoning may reinforce rather than correct. Consequently, subtle distortions in trait perception can cascade into high-stakes outcomes, including the severity of sentencing and danger classification. We conclude that implementing linear sequential unmasking and structured justification protocols is essential to safeguard the integrity of assessments. These procedural adjustments offer a robust framework for improving forensic objectivity.